Pesan Moral Dalam Lirik Lagu Mangku Purel Karya Nur Bayan: Indonesia - Ardiansyah, Muhammad; Hariyanto, Didik (Pahlawan 12 Press, 2023)
ABSTRACT Song Mangku Purel by Nur Bayan became the song that was most popular with singers and occupied the first trending position on YouTube in November 2022. There are positive and negative comments about the song. This research aims to find out the moral message that is in the lyrics of the song Mangku Purel Karya Nur Bayan. The study used a qualitative approach with observational data collection techniques, listening to Mangku Purel's song on the YouTube video